Orchid diversity along an altitudinal gradient in the central Balkans - Djordjević, Vladan; Tsiftsis, Spyros; Kindlmann, Pavel; Stevanović, Vladimir (Frontiers in Ecology and Evolution, 2022)
Understanding patterns of species diversity along an altitudinal gradient is the major topic of much biogeographical and ecological research. The aim of this study was to explore how richness and density of orchid species and subspecies in terms of different categories of underground organ systems and pollination systems vary along an altitudinal gradient in the central Balkans. The altitudinal gradient of the study area was divided into 21 100-m vertical intervals. Data were analyzed using both non-linear and linear regressions with three data sets (total orchids, orchids of forest habitats, orchids of non-forest habitats) in the case of species richness and three data sets (total orchids – total area, forest orchids – forest area, and orchids of non-forest habitats – non-forest area) in the case of species density. The results showed a hump-shaped pattern of orchid richness and density, peaking at 900 to 1,000 m. The richness and density of orchids of forest habitats are generally slightly greater than the richness and density of orchids of non-forest habitats in lowland areas, whereas the orchids of herbaceous vegetation types dominating at high altitudes. Tuberous orchids dominate in low and mid-altitude areas, orchids with palmately lobed and fusiform tubers ("intermediate orchids") dominate at high altitudes, while rhizomatous orchids are predominate in mid-altitude forest stands. Both deceptive and self-pollinated orchids show a unimodal trend with a peak at mid-altitude areas. This study underlines the importance of low and mid-altitude areas for the survival of deceptive orchids and the importance of mid- and high-altitude areas for the survival of rewarding orchids. In addition, forest habitats at mid-altitudes have been shown to be crucial for the survival of self-pollinated orchids. The results suggest that the altitudinal patterns of orchid richness and density in the central Balkans are determined by mechanisms related to land area size and habitat cover, partially confirming the species-area relationship (SAR) hypothesis. This study contributes significantly to a better understanding of the potential impacts of habitat changes on orchid diversity, thereby facilitating more effective conservation planning.